PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, GROWTH, LIKUIDITAS DAN SIZE TERHADAP NILAI PERUSAHAAN PADA INDUSTRI TEKSTIL DAN GARMEN DI BURSA EFEK INDONESIA - Yuslirizal, Andhika (Katalogis, 2017)
The study aims to determine and analyze the influence of managerial ownerships institutional ownership, growth, liquidity, and size on company’s valus in textile and garment industry listed on Indonesia stock exchange 2009-2016. Population consist of 19 textile and garment companies and sample 14 companies selected througth purposive random sampling method. Analysis technique is multiple linear regressions to obtain comprehensive description between variables. Test results show that managerial ownership partially have positive but insignificant inflence on company’s value, institutional ownerships and liquidity have postive and significant influence on company’s value, while growth and size have negative and insignificant influence on company’s value. The ability of variables topredict the value of the company 1s 29,2% while the remaining 70,8% influenced by other that are no studied.